Pembinaan Kelompok Pembenihan Ikan Lele Melalui Penerapan Teknologi Semi Intensif di Kecamatan Gabuswetan, Kabupaten Indramayu, Jawa Barat - Jeniarty Rani Saranga; Yenni Nuraini; Rina Rina; Lenny S Syafei (Unri Conference Series: Community Engagement, 2021)
Gabuswetan District is one of the centers for catfish hatchery in the Indramayu Regency. In the seed production process, there are obstacles, namely the lack of knowledge of farmers on good fish hatchery methods so that the survival rate of seeds is low which results in unfulfilled market demand. This activity was conducted from March 11 to May 24, 2019 with cultivators as respondents in Sekarmulya Village, Gabuswetan District, Indramayu. The purpose of this activity is to increase the knowledge, skills, and attitudes of farmers on good fish hatchery methods through the application of semi-intensive technology by delivering counseling using demonstration methods and making pilot ponds. The results showed an increase in knowledge, attitudes, and skills of the target, namely cultivators after the demonstration activity was carried out by involving the target directly in the production process. In the final stage of innovation adoption, two cultivators apply the given innovation.